Hadith #2164 - Sunan Abi Dawud - Anas ibn Malik; Hammad bin Zayd حماد بن زيد بن درهم الأزدي الأزرق; Musa bin Isma'il al-Munqari al-Tabudhaki موسى بن إسماعيل المنقري - لتبوذكي; Thabit bin Aslam Albanani ثابت بن أسلم البناني (Sunan Abi Dawud)
Ibn Umar misunderstood (the Qur’anic verse, “So come to your tilth however you will”)–may Allah forgive him. The fact is that this clan of the Ansar, who were idolaters, lived in the company of the Jews who were the people of the Book. They (the Ansar) accepted their superiority over themselves in respect of knowledge, and they followed most of their actions. The people of the Book (i.e. the Jews) used to have intercourse with their women on one side alone (i.e. lying on their backs). Th
Grade: Hasan

Hadith #2327 - Sunan Abi Dawud - Hammad bin Zayd حماد بن زيد بن درهم الأزدي الأزرق; Imran bin Husain; Matruf bin Tarayf al-Harithi مطرف بن طريف; Musa bin Isma'il al-Munqari al-Tabudhaki موسى بن إسماعيل المنقري - لتبوذكي; Sa'id bin Iyas al-Jariri سعيد بن إياس الجريري; Thabit bin Aslam Albanani ثابت بن أسلم البناني (Sunan Abi Dawud)
The Prophet (ﷺ) said: Do not fast one day or two days just before Ramadan except in the case of a man who has been in the habit or observing a fast (on that day); and do not fast until you sight it (the moon). Then fast until you sight it. If a cloud appears on that day (i.e. 29th of Ramadan) then complete the number thirty (days) and then end the fasting: a month consists of twenty-nine days.
Grade: Sahih

Hadith #2355 - Sunan Abi Dawud - Abdur-Razzaq عبد الرزاق بن همام; Ahmad bin Hanbal أحمد بن حنبل; Anas ibn Malik; Ja'far bin Sulaiman al-Daba'i جعفر بن سليمان الضبعي; Thabit bin Aslam Albanani ثابت بن أسلم البناني (Sunan Abi Dawud)
The Prophet (ﷺ) said: When one of you is fasting, he should break his fast with dates; but if he cannot get any, then (he should break his fast) with water, for water is purifying.
Grade: Hasan Sahih

Hadith #2374 - Sunan Abi Dawud - Abdullah bin Muslima al-Qa'nabi عبد الله بن مسلمة بن قعنب القعنبي; Sulaiman bin al-Mughira al-Qaysy سليمان بن المغيرة القيسي مولاهم; Thabit bin Aslam Albanani ثابت بن أسلم البناني (Sunan Abi Dawud)
A man from the Companions of the Prophet (ﷺ) told me that the Messenger of Allah (ﷺ) prohibited cupping and perpetual fasting, but he had not made them unlawful showing mercy on his Companions. Thereupon he was asked: Messenger of Allah, you observe perpetual fast till dawn. He replied: I observe perpetual fast till dawn (for) my Lord gives me food and drink.
Grade: Sahih

Hadith #2462 - Sunan Abi Dawud - Abu Rafi'; Hammad bin Zayd حماد بن زيد بن درهم الأزدي الأزرق; Musa bin Isma'il al-Munqari al-Tabudhaki موسى بن إسماعيل المنقري - لتبوذكي; Thabit bin Aslam Albanani ثابت بن أسلم البناني; Ubayy ibn Ka'b (Sunan Abi Dawud)
The Prophet (ﷺ) used to observe retirement (i’tikaf) to the mosque during the last ten days of Ramadan till Allah took him, and then his wives observed retirement to the mosque after his death.
Grade: Sahih

Hadith #2530 - Sunan Abi Dawud - Abd al-Salam bin Mthr عبد السلام بن مطهر بن حسام; Anas ibn Malik; Ja'far bin Sulaiman al-Daba'i جعفر بن سليمان الضبعي; Thabit bin Aslam Albanani ثابت بن أسلم البناني (Sunan Abi Dawud)
A man emigrated to the Messenger of Allah (ﷺ) from the Yemen. He asked (him): Have you anyone (of your relatives) in the Yemen? He replied: My parents. He asked: Did they permit you? He replied: No. He said: Go back to them and ask for their permission. If they permit you, then fight (in the path of Allah), otherwise be devoted to them.
Grade: Sahih

Hadith #2617 - Sunan Abi Dawud - Anas ibn Malik; Harun bin 'Abdullah al-Hamal هارون بن عبد الله بن مروان الحمال; Hashim bin al-Qasim bin Muslim هاشم بن القاسم أبو النضر - قيصر; Sulaiman bin al-Mughira al-Qaysy سليمان بن المغيرة القيسي مولاهم; Thabit bin Aslam Albanani ثابت بن أسلم البناني (Sunan Abi Dawud)
Abu Mishar was told about Ubna. He said “We know it better. This is Yubna of Palestine.
Grade: Sahih

Hadith #2633 - Sunan Abi Dawud - Anas ibn Malik; Hammad bin Zayd حماد بن زيد بن درهم الأزدي الأزرق; Musa bin Isma'il al-Munqari al-Tabudhaki موسى بن إسماعيل المنقري - لتبوذكي; Thabit bin Aslam Albanani ثابت بن أسلم البناني (Sunan Abi Dawud)
Ibn ‘Awn said “I wrote to Nafi’ asking him about summoning the polytheists (to Islam) at the time of fighting. So, he wrote to me “This was in the early days of Islam. The Prophet of Allaah(ﷺ) attacked Banu Al Mustaliq while they were inattentive and their cattle were drinking water. So their fighters were killed and the survivors (i.e., women and children) were taken prisoners. On that day Juwairiyyah daughter of Al Harith was obtained. ‘Abd Allaah narrated this to me, he was in tha
Grade: Sahih

Hadith #2680 - Sunan Abi Dawud - Anas ibn Malik; Hammad bin Zayd حماد بن زيد بن درهم الأزدي الأزرق; Musa bin Isma'il al-Munqari al-Tabudhaki موسى بن إسماعيل المنقري - لتبوذكي; Thabit bin Aslam Albanani ثابت بن أسلم البناني (Sunan Abi Dawud)
Yahya ibn Abdullah said: When the captives (of the battle of Badr) were brought, Sawdah daughter of Zam’ah was present with the children of Afra’ at the halting place of their camels, that is, Awf and Mu’awwidh sons of Afra’. This happened before the prescription of veil for them. Sawdah said: I swear by Allah, I was with them when I came (from there to the people) and I was told: These are captives recently brought (here). I returned to my house, and the Messenger of Allah (ﷺ) was the
Grade: Hasan

Hadith #2687 - Sunan Abi Dawud - Anas ibn Malik; Hammad bin Zayd حماد بن زيد بن درهم الأزدي الأزرق; Musa bin Isma'il al-Munqari al-Tabudhaki موسى بن إسماعيل المنقري - لتبوذكي; Thabit bin Aslam Albanani ثابت بن أسلم البناني (Sunan Abi Dawud)
We fought along with AbdurRahman ibn Khalid ibn al-Walid. Four infidels from the enemy were brought to him. He commanded about them and they were killed in confinement. Abu Dawud said: The narrators other than Sa’id reported from Ibn Wahb in this tradition: “(killed him) with arrows in confinement.” When Abu Ayyub al-Ansari was informed about it, he said: I heard the Messenger of Allah (ﷺ) prohibiting to kill in confinement. By Him in Whose hands my soul is, if there were a hen, I would
Grade: Da'if

Hadith #2779 - Sunan Abi Dawud - Anas ibn Malik; Hammad bin Zayd حماد بن زيد بن درهم الأزدي الأزرق; Musa bin Isma'il al-Munqari al-Tabudhaki موسى بن إسماعيل المنقري - لتبوذكي; Thabit bin Aslam Albanani ثابت بن أسلم البناني (Sunan Abi Dawud)
Al Sai’ib bin Yazid said “When the Prophet(ﷺ) turned from the battle of Tabuk to Madeenah, the people received him, I met him along with the children at Thaniyyat Al Wada’.
Grade: Sahih

Hadith #2996 - Sunan Abi Dawud - Anas ibn Malik; Hammad bin Zayd حماد بن زيد بن درهم الأزدي الأزرق; Thabit bin Aslam Albanani ثابت بن أسلم البناني (Sunan Abi Dawud)
Anas bin Malik said “Safiyyah first fell to Dihyat Al Kalbi, the she fell to the Apostle of Allaah(ﷺ).
Grade: Sahih

Hadith #3023 - Sunan Abi Dawud - Abdullah bin Rbah عبد الله بن رباح الأنصاري أبو خالد; Abu Hurairah; Muslim bin Ibrahim al-Azdy مسلم بن إبراهيم الأزدي الفراهيدي; Salam bin Mskyn bin Rabi'ya سلام بن مسكين بن ربيعة; Thabit bin Aslam Albanani ثابت بن أسلم البناني (Sunan Abi Dawud)
Wahb bin Munabbih said “I sked Jabir “Did they get any booty on the day of conquest (of Makkah)? He replied, No.
Grade: Sahih

Hadith #3094 - Sunan Abi Dawud - Anas ibn Malik; Hammad bin Zayd حماد بن زيد بن درهم الأزدي الأزرق; Sulaiman bin Harb سليمان بن حرب; Thabit bin Aslam Albanani ثابت بن أسلم البناني (Sunan Abi Dawud)
The Messenger of Allah (ﷺ) went out to visit ‘Abd Allah b. Ubayy during his illness of which he died. When he entered upon him, he realised death on him. He said: I used to forbid you from the love of Jews. He (‘Abd Allah) said: As’ad b. Zurarah hated them. So what (the benefited) ? When he died, his son came and said: Prophet of Allah, ‘Abd Allah b. Ubayy has died, give me your shirt, so that I shroud him in it. The Messenger of Allah (ﷺ) took off his shirt and gave it to him.
Grade: Da'if

Hadith #3096 - Sunan Abi Dawud - al-Fadl bin Dlhm al-Wasty الفضل بن دلهم الواسطي ثم البصري القصاب; al-Rabi' bin Rwh الربيع بن روح; Anas ibn Malik; Muhammad bin Awf bin Sufyan محمد بن عوف بن سفيان الطائي; Muhammad bin Khalid bin محمد بن خالد; Thabit bin Aslam Albanani ثابت بن أسلم البناني (Sunan Abi Dawud)
The Prophet (ﷺ) would visit me (during my illness) riding neither a mule nor a pony.
Grade: Sahih

Hadith #3118 - Sunan Abi Dawud - Hammad bin Zayd حماد بن زيد بن درهم الأزدي الأزرق; Musa bin Isma'il al-Munqari al-Tabudhaki موسى بن إسماعيل المنقري - لتبوذكي; Thabit bin Aslam Albanani ثابت بن أسلم البناني; Umm Salamah (Sunan Abi Dawud)
When the Messenger of Allah (ﷺ) entered upon Abu Salamah, his eyes were fixedly open. So he closed them. The members of his family cried. He said: Do not pray for yourself anything but good, for the angels utter Amin to what you say. He then said: O Allah, forgive Abu Salamah, raise his rank among those who are guided, and grant him a succession in his descendants who remain. Forgive both us and him, Lord of the universe. O Allah,make his grave spacious for him, and grant him light in it. Abu
Grade: Sahih

Hadith #3123 - Sunan Abi Dawud - Anas ibn Malik; Muhammad bin al-Muthna - al-Zaman محمد بن المثنى أبو موسى - الزمن; Shu'bah bin al-Hajjaj شعبة بن الحجاج; Thabit bin Aslam Albanani ثابت بن أسلم البناني; Uthman bin 'Umar bin Fars عثمان بن عمر بن فارس (Sunan Abi Dawud)
We buried a deceased person in the company of the Messenger of Allah (ﷺ). When we had finished, the Messenger of Allah (ﷺ) returned and we also returned with him. When he approached his door, he stopped, and we saw a woman coming towards him. He (the narrator) said: I think he recognized her. When she went away, we came to know that she was Fatimah. The Messenger of Allah (ﷺ) said to her: What brought you out of your house, Fatimah? She replied: I came to the people of this house, Messenge
Grade: Hasan

Hadith #3125 - Sunan Abi Dawud - Anas ibn Malik; Shayban bin Farroukh شيبان بن فروخ / أبي شيبة; Sulaiman bin al-Mughira al-Qaysy سليمان بن المغيرة القيسي مولاهم; Thabit bin Aslam Albanani ثابت بن أسلم البناني (Sunan Abi Dawud)
A daughter of Messenger of Allah (ﷺ) sent him message while I and Sa’d were with him and I think Ubayy was also there: My son or daughter (the narrator is doubtful) is dying, so come to us. He sent her greeting, saying at the same time: Say! What Allah has been taken belongs to Him, what He has given (belongs to Him), and He has appointed time for everything. She then sent a message adjuring him (to come to her). So he came to her and the child who was on the point of death was placed in the
Grade: Sahih

Hadith #3202 - Sunan Abi Dawud - Abu Hurairah; Abu Rafi'; Hammad bin Zayd حماد بن زيد بن درهم الأزدي الأزرق; Masdad bin Masrhad مسدد بن مسرهد بن مسربل; Sulaiman bin Harb سليمان بن حرب; Thabit bin Aslam Albanani ثابت بن أسلم البناني (Sunan Abi Dawud)
The Messenger of Allah (ﷺ) led us in prayer over bier of a Muslim and I heard him say: O Allah, so and so, son of so and so, is in Thy protection, so guard him from the trial in the grave. (AbdurRahman in his version said: “In Thy protection and in Thy nearer presence, so guard him from the trial in the grave) and the punishment in Hell. Thou art faithful and worthy of praise. O Allah, forgive him and show him mercy. Thou art the forgiving and the merciful one.” AbdurRahman said: “On the
Grade: Sahih

Hadith #3221 - Sunan Abi Dawud - Abdur-Razzaq عبد الرزاق بن همام; Anas ibn Malik; Ma'mar bin Rashid معمر بن راشد; Thabit bin Aslam Albanani ثابت بن أسلم البناني; Yahya bin Musa Khat يحيى بن موسى خت (Sunan Abi Dawud)
Whenever the Prophet (ﷺ) became free from burying the dead, he used to stay at him (i.e. his grave) and say: Seek forgiveness for your brother, and beg steadfastness for him, for he will be questioned now. Abu Dawud said: The full name of the narrator Buhair is Buhair b. Raisan.
Grade: Sahih

Hadith #3300 - Sunan Abi Dawud - Anas ibn Malik; Hameed bin Abi Hameed حميد بن أبي حميد الطويل; Masdad bin Masrhad مسدد بن مسرهد بن مسربل; Thabit bin Aslam Albanani ثابت بن أسلم البناني; Yahya bin Sa'id bin Farroukh al-Qatan يحيى بن سعيد بن فروخ القطان (Sunan Abi Dawud)
While the Prophet (ﷺ) was preaching a man was standing in the sun. He asked about him. They said: He is Abu Isra’il who has taken a vow to stand and not to sit, or go into shade, or speak, but to fast. Thereupon he said: Command him to speak, to go into the shade, sit and complete his fast.
Grade: Sahih

Hadith #3450 - Sunan Abi Dawud - Affan bin Muslim عفان بن مسلم بن عبد الله الصفار; Anas ibn Malik; Hameed bin Abi Hameed حميد بن أبي حميد الطويل; Hammad bin Salama حماد بن سلمة; Qatada قتادة; Thabit bin Aslam Albanani ثابت بن أسلم البناني; Uthman bin Muhammad (Sunan Abi Dawud)
A man came and said: Messenger of Allah, fix prices. He said: (No), but I shall pray. Again the man came and said: Messenger of Allah, fix prices. He said: It is but Allah Who makes the prices low and high. I hope that when I meet Allah, none of you has any claim on me for doing wrong regarding blood or property.
Grade: Sahih

Hadith #3672 - Sunan Abi Dawud - Anas ibn Malik; Hammad bin Zayd حماد بن زيد بن درهم الأزدي الأزرق; Sulaiman bin Harb سليمان بن حرب; Thabit bin Aslam Albanani ثابت بن أسلم البناني (Sunan Abi Dawud)
The Quranic verse :”O ye who believe ,approach not prayer with minds befogged until you can understand all they say,” and the verse: “They ask thee concerning wine and gambling. Say: In them is great sin and some profit for men ,” were repeated by the verse in Surat al-Ma’idah: ”O ye who believe, intoxicants and gambling,(dedication) stones.
Grade: Hasan

Hadith #3742 - Sunan Abi Dawud - Hammad bin Zayd حماد بن زيد بن درهم الأزدي الأزرق; Masdad bin Masrhad مسدد بن مسرهد بن مسربل; Qutayba bin Sa'id bin Jamil قتيبة بن سعيد بن جميل; Thabit bin Aslam Albanani ثابت بن أسلم البناني (Sunan Abi Dawud)
The worst kind of food is that at a wedding feast to which the rich are invited and from which the poor are left out. If anyone does not attend the feast to which he was invited, he has disobeyed Allah and His Apostle (may peace upon him).
Grade: Sahih

Hadith #3769 - Sunan Abi Dawud - Hammad bin Zayd حماد بن زيد بن درهم الأزدي الأزرق; Musa bin Isma'il al-Munqari al-Tabudhaki موسى بن إسماعيل المنقري - لتبوذكي; Thabit bin Aslam Albanani ثابت بن أسلم البناني (Sunan Abi Dawud)
I do not eat while reclining.
Grade: Sahih

Hadith #3844 - Sunan Abi Dawud - Anas ibn Malik; Hammad bin Zayd حماد بن زيد بن درهم الأزدي الأزرق; Musa bin Isma'il al-Munqari al-Tabudhaki موسى بن إسماعيل المنقري - لتبوذكي; Thabit bin Aslam Albanani ثابت بن أسلم البناني (Sunan Abi Dawud)
when a fly alights in anyone’s vessel, he should plunge it all in, for in one of its wings there is a disease, and in the other is a cure. It prevents the wing of it is which there is a cure, so plunge it all in (the vessel).
Grade: Sahih

Hadith #3853 - Sunan Abi Dawud - Abdur-Razzaq عبد الرزاق بن همام; Anas ibn Malik; Ma'mar bin Rashid معمر بن راشد; Mkhld bin Khalid bin Yazid مخلد بن خالد بن يزيد الشعيري; Thabit bin Aslam Albanani ثابت بن أسلم البناني (Sunan Abi Dawud)
AbulHaytham ibn at-Tayhan prepared food for the Messenger of Allah (ﷺ), and he invited the Prophet (ﷺ) and his Companions. When they finished (food), the said: If some people enter the house of a man, his food is eaten and his drink is drunk, and they supplicate (to Allah) for him, this is his reward.
Grade: Da'if

Hadith #3864 - Sunan Abi Dawud - Hammad bin Zayd حماد بن زيد بن درهم الأزدي الأزرق; Imran bin Husain; Matruf bin Tarayf al-Harithi مطرف بن طريف; Musa bin Isma'il al-Munqari al-Tabudhaki موسى بن إسماعيل المنقري - لتبوذكي; Thabit bin Aslam Albanani ثابت بن أسلم البناني (Sunan Abi Dawud)
The Prophet (ﷺ) sent a physician to Ubayy (ibn Ka’b), and he cut his vein.
Grade: Sahih

Hadith #3981 - Sunan Abi Dawud - Asma' bint Yazid bin al-Sakan; Hammad bin Zayd حماد بن زيد بن درهم الأزدي الأزرق; Musa bin Isma'il al-Munqari al-Tabudhaki موسى بن إسماعيل المنقري - لتبوذكي; Shar bin Hushab al-Asha'ri شهر بن حوشب الأشعري; Thabit bin Aslam Albanani ثابت بن أسلم البناني (Sunan Abi Dawud)
Ubayy ibn Ka’b) said: The Prophet (ﷺ) read the verse: “Say: In the bounty of Allah and in His mercy–in that let you rejoice: that is better than the wealth you hoard.”
Grade: Hasan Sahih

Hadith #3982 - Sunan Abi Dawud - Abdul 'Aziz bin al-Mukhtar عبد العزيز بن المختار; Fdyl bin Husayn bin Talha فضيل بن حسين بن طلحة; Shar bin Hushab al-Asha'ri شهر بن حوشب الأشعري; Thabit bin Aslam Albanani ثابت بن أسلم البناني (Sunan Abi Dawud)
She heard the Prophet (ﷺ) read the verse: “He acted unrighteously.” (innahu ‘amila ghayra salih).
Grade: Sahih

Hadith #4033 - Sunan Abi Dawud - Amarh bin Zadhan al-Sydlany عمارة بن زاذان الصيدلاني أبو سلمة البصري; Amr bin 'Awn/'Auf bin Aws; Anas ibn Malik; Thabit bin Aslam Albanani ثابت بن أسلم البناني (Sunan Abi Dawud)
My father said to me: My son, if you had seen us while we were with the Messenger of Allah (ﷺ) and the rain had fallen on us, you would have thought that our smell was the smell of the sheep.
Grade: Sahih

Hadith #4105 - Sunan Abi Dawud - Anas ibn Malik; Muhammad bin 'Isa bin Hyan محمد بن عيسى بن حيان; Thabit bin Aslam Albanani ثابت بن أسلم البناني (Sunan Abi Dawud)
Umm Salamah asked the Messenger of Allah (ﷺ) permission for getting herself cupped. He commanded Abu Tibah to cup her. The transmitter said: I think he was her foster-brother or a boy not yet of age.
Grade: Sahih

Hadith #4184 - Sunan Abi Dawud - Abdur-Razzaq عبد الرزاق بن همام; Anas ibn Malik; Ma'mar bin Rashid معمر بن راشد; Mkhld bin Khalid bin Yazid مخلد بن خالد بن يزيد الشعيري; Thabit bin Aslam Albanani ثابت بن أسلم البناني (Sunan Abi Dawud)
The Messenger of Allah (ﷺ) had hair which reached the lobes of his ears.
Grade: Sahih

Hadith #4195 - Sunan Abi Dawud - Abu Karayb, Muhammad bin al-'Ala' محمد بن العلاء - أبو كريب; Anas ibn Malik; Thabit bin Aslam Albanani ثابت بن أسلم البناني; Zayd bin al-Habab al-'Akli زيد بن الحباب أبو الحسين العكلي (Sunan Abi Dawud)
The Prophet (ﷺ) saw a boy with part of his head shaved and part left unshaven. He forbade them to do that, saying: Shave it all or leave it all.
Grade: Sahih

Hadith #4208 - Sunan Abi Dawud - Anas ibn Malik; Hammad bin Zayd حماد بن زيد بن درهم الأزدي الأزرق; Muhammad bin 'Ubaid al-Tanafasi محمد بن عبيد بن أبي أمية الطنافسي; Thabit bin Aslam Albanani ثابت بن أسلم البناني (Sunan Abi Dawud)
I and my father came to the Prophet (ﷺ). He said to a man or to my father: Who is this? He replied: He is my son. He said: Do not commit a crime on him. He had stained his beard with henna.
Grade: Sahih

Hadith #4365 - Sunan Abi Dawud - Anas ibn Malik; Hameed bin Abi Hameed حميد بن أبي حميد الطويل; Hammad bin Zayd حماد بن زيد بن درهم الأزدي الأزرق; Musa bin Isma'il al-Munqari al-Tabudhaki موسى بن إسماعيل المنقري - لتبوذكي; Qatada قتادة; Thabit bin Aslam Albanani ثابت بن أسلم البناني (Sunan Abi Dawud)
So he (the prophet) order nails to be heated and had them blinded with them, and he had their hands and feet cut off, and did not cauterise them to stop the flow of blood.
Grade: Sahih

Hadith #4366 - Sunan Abi Dawud - Anas ibn Malik; Hisham bin Abi 'Abdullah al-Dastawa'i هشام بن أبي عبد الله الدستوائي; Muhammad bin Abi 'Adi محمد بن أبي عدي; Muhammad bin Bashar Bindar محمد بن بشار بندار; Qatada قتادة; Shu'bah bin al-Hajjaj شعبة بن الحجاج; Thabit bin Aslam Albanani ثابت بن أسلم البناني (Sunan Abi Dawud)
The Messenger of Allah (ﷺ) sent some people who were experts in tracking in pursuit of them and they were brought (to him). Allah , the Exalted, then revealed the verse about it : “ The punishment of those who wage war against Allah and his Apostle and strive for mischief through the land.
Grade: Sahih

Hadith #4600 - Sunan Abi Dawud - Aisha bint Abi Bakr; Hammad bin Zayd حماد بن زيد بن درهم الأزدي الأزرق; Musa bin Isma'il al-Munqari al-Tabudhaki موسى بن إسماعيل المنقري - لتبوذكي; Thabit bin Aslam Albanani ثابت بن أسلم البناني (Sunan Abi Dawud)
I heard Ka`b b. Malik – the transmitter Ibn al-Sarh then narrated the story of his remaining behind from the Prophet (ﷺ) during the campaign of Tabuk – say: The Messenger of Allah (ﷺ) forbade the Muslims to speak to any of us three. When (in this state) abundant time passed on me, I ascended the wall of the garden of Abu Qatadah who was my cousin. I saluted him, but, I swear by Allah, he did not return salute to me. He then narrated the story of the revelation of the Qur’anic verses re
Grade: Sahih

Hadith #4716 - Sunan Abi Dawud - Anas ibn Malik; Hammad bin Zayd حماد بن زيد بن درهم الأزدي الأزرق; Musa bin Isma'il al-Munqari al-Tabudhaki موسى بن إسماعيل المنقري - لتبوذكي; Thabit bin Aslam Albanani ثابت بن أسلم البناني (Sunan Abi Dawud)
In our opinion it means that covenant which Allah had taken in the loins of their fathers when He said : “Am I not your Lord? They said: Yes.
Grade: Sahih

Hadith #4717 - Sunan Abi Dawud - Anas ibn Malik; Hammad bin Zayd حماد بن زيد بن درهم الأزدي الأزرق; Musa bin Isma'il al-Munqari al-Tabudhaki موسى بن إسماعيل المنقري - لتبوذكي; Thabit bin Aslam Albanani ثابت بن أسلم البناني (Sunan Abi Dawud)
The woman who buries alive her new-born girl and the girl who is buried alive both will go to Hell. This tradition has also been transmitted by Ibn Mas’ud from the Prophet (May peace be upon him) to the same effect through a different chain of narrators.
Grade: Sahih

Hadith #4772 - Sunan Abi Dawud - Abdullah bin Muslima al-Qa'nabi عبد الله بن مسلمة بن قعنب القعنبي; Anas ibn Malik; Sulaiman bin al-Mughira al-Qaysy سليمان بن المغيرة القيسي مولاهم; Thabit bin Aslam Albanani ثابت بن أسلم البناني (Sunan Abi Dawud)
The Prophet (ﷺ) said: He who is killed while protecting his property is a martyr, and he who is killed while defending his family, or his blood, or his religion is a martyr.
Grade: Sahih

Hadith #4792 - Sunan Abi Dawud - Ahmed bin Manay' أحمد بن منيع; Amr bin al-Hythm bin Qtn عمرو بن الهيثم بن قطن; Anas ibn Malik; Thabit bin Aslam Albanani ثابت بن أسلم البناني (Sunan Abi Dawud)
A man asked permission to see the Prophet (ﷺ), and the Prophet (ﷺ) said: He is a bad member of the tribe. When he entered, the Messenger of Allah (ﷺ) treated in a frank and friendly way and spoke to him. When he departed , I said: Messenger of Allah! When he asked permission, you said: He is a bad member of the tribe, but when he entered, you treated him in a frank and friendly way. The Messenger of Allah replied: Aisha! Allah does not like the one who is unseemly and lewd in his language
Grade: Hasan Sahih

Hadith #4800 - Sunan Abi Dawud - Anas ibn Malik; Hammad bin Zayd حماد بن زيد بن درهم الأزدي الأزرق; Musa bin Isma'il al-Munqari al-Tabudhaki موسى بن إسماعيل المنقري - لتبوذكي; Thabit bin Aslam Albanani ثابت بن أسلم البناني (Sunan Abi Dawud)
The Prophet (ﷺ) said: I guarantee a house in the surroundings of Paradise for a man who avoids quarrelling even if he were in the right, a house in the middle of Paradise for a man who avoids lying even if he were joking, and a house in the upper part of Paradise for a man who made his character good.
Grade: Hasan

Hadith #4810 - Sunan Abi Dawud - Anas ibn Malik; Hammad bin Zayd حماد بن زيد بن درهم الأزدي الأزرق; Musa bin Isma'il al-Munqari al-Tabudhaki موسى بن إسماعيل المنقري - لتبوذكي; Thabit bin Aslam Albanani ثابت بن أسلم البناني (Sunan Abi Dawud)
The Prophet (ﷺ) said: There is hesitation in everything except in the actions of the next world.
Grade: Sahih

Hadith #4817 - Sunan Abi Dawud - Anas ibn Malik; Hammad bin Salama حماد بن سلمة; Thabit bin Aslam Albanani ثابت بن أسلم البناني; Uthman bin Muhammad; Yazid bin Harun يزيد بن هارون (Sunan Abi Dawud)
The Prophet (ﷺ) said: the same occasion: Help the oppressed (sorrowful) and guide those who have lost their way.
Grade: Sahih

Hadith #4885 - Sunan Abi Dawud - Abdur Rahman bin Ajlan عبد الرحمن بن عجلان; Hammad bin Zayd حماد بن زيد بن درهم الأزدي الأزرق; Musa bin Isma'il al-Munqari al-Tabudhaki موسى بن إسماعيل المنقري - لتبوذكي; Thabit bin Aslam Albanani ثابت بن أسلم البناني (Sunan Abi Dawud)
A desert Arab came and making his camel kneel and tethering it, entered the mosque and prayed behind the Messenger of Allah (ﷺ). When The Messenger of Allah (ﷺ) had given the salutation, he went to his riding beast and, after untethering and riding it, he called out: O Allah, show mercy to me and to Muhammad and associate no one else in Thy mercy to us. The Messenger of Allah (ﷺ) then said: Do you think that he or his camel is farther astray? Did you not listen to what he said? They replie
Grade: Da'if

Hadith #4921 - Sunan Abi Dawud - Abdur-Razzaq عبد الرزاق بن همام; al-Hasan bin 'Ali al-Halwani الحسن بن علي الخلال الحلواني; Anas ibn Malik; Ma'mar bin Rashid معمر بن راشد; Thabit bin Aslam Albanani ثابت بن أسلم البناني (Sunan Abi Dawud)
I did not hear the Messenger of Allah (ﷺ) making a concession for anything people say falsely except in three matters. The Messenger of Allah (ﷺ) would say: I do not count as a liar a man who puts things right between people, saying a word by which he intends only putting things right, and a man who says something in war, and a man who says something to his wife, or a wife who says something to her husband.
Grade: Sahih

Hadith #4949 - Sunan Abi Dawud - Anas ibn Malik; Hammad bin Salama حماد بن سلمة; Musa bin Isma'il al-Munqari al-Tabudhaki موسى بن إسماعيل المنقري - لتبوذكي; Thabit bin Aslam Albanani ثابت بن أسلم البناني (Sunan Abi Dawud)
Your names which are dearest to Allah are ‘Abd Allah and ‘Abd al-Rahman.
Grade: Sahih

Hadith #4967 - Sunan Abi Dawud - Anas ibn Malik; Hammad bin Zayd حماد بن زيد بن درهم الأزدي الأزرق; Musa bin Isma'il al-Munqari al-Tabudhaki موسى بن إسماعيل المنقري - لتبوذكي; Thabit bin Aslam Albanani ثابت بن أسلم البناني (Sunan Abi Dawud)
I said: Messenger of Allah! tell me if a son is born to me after your death, may I give him your name and your kunyah? He replied: Yes. The transmitter Abu Bakr did not mention the words “I said”. Instead, he said: ‘Ali said to the Prophet (ﷺ).
Grade: Sahih

Hadith #5023 - Sunan Abi Dawud - Anas ibn Malik; Hammad bin Zayd حماد بن زيد بن درهم الأزدي الأزرق; Musa bin Isma'il al-Munqari al-Tabudhaki موسى بن إسماعيل المنقري - لتبوذكي; Thabit bin Aslam Albanani ثابت بن أسلم البناني (Sunan Abi Dawud)
I heard the Messenger of Allah (May peace be upon him) say : He who sees me in a dream will see me when awake or as if he will see me when awake, for the devil does not take my likeness.
Grade: Sahih

Hadith #5051 - Sunan Abi Dawud - Anas ibn Malik; Hammad bin Salama حماد بن سلمة; Thabit bin Aslam Albanani ثابت بن أسلم البناني; Uthman bin Muhammad; Yazid bin Harun يزيد بن هارون (Sunan Abi Dawud)
when the prophet (May peace be upon him) went to his bed, he used to say : O Allah! Lord of the heavens, Lord of the earth, Lord of everything, who splittest the grain and the kernel, who hast sent down the Torah, forelock Thou seizes. Thou art the first and there is nothing before thee; Thou art the Last and there is nothing after Thee; Thou art the Outward and there is nothing above Thee; Thou art the Inward and there is nothing below Thee. Wahb added in his version : pay the debt for me and g
Grade: Sahih

Hadith #5098 - Sunan Abi Dawud - Anas ibn Malik; Ja'far bin Sulaiman al-Daba'i جعفر بن سليمان الضبعي; Qutayba bin Sa'id bin Jamil قتيبة بن سعيد بن جميل; Thabit bin Aslam Albanani ثابت بن أسلم البناني (Sunan Abi Dawud)
I never saw the Messenger of Allah (May peace be upon him) laugh fully to such an extent that I could see his uvula. He would only smile, and when he saw clouds or wind, his face showed signs (of fear). I asked him: Messenger of Allah! When the people see the cloud, they rejoice, hoping for that it may contain rain, and I notice that when you see it, (the signs of) abomination on your face. He replied: ‘A’ishah! What gives me safety from the fact that it might contain punishment? A people we
Grade: Sahih

Hadith #5123 - Sunan Abi Dawud - Anas ibn Malik; Muslim bin Ibrahim al-Azdy مسلم بن إبراهيم الأزدي الفراهيدي; Thabit bin Aslam Albanani ثابت بن أسلم البناني (Sunan Abi Dawud)
AbdurRahman ibn AbuUqbah quoted his father AbuUqbah who was a client from the people of Persia as saying: I was present at Uhud along with the Messenger of Allah (ﷺ), and on smiting one of the polytheists I said: Take this from me who is the young Persian. The Messenger of Allah (ﷺ) then turned to me and said: Why did you not say: Take this from me who is the young Ansari?
Grade: Da'if

Hadith #5125 - Sunan Abi Dawud - Anas ibn Malik; Khalid bin 'Abdullah al-Tahan خالد بن عبد الله بن عبد الرحمن الطحان; Thabit bin Aslam Albanani ثابت بن أسلم البناني; Wahb bin Bqyh bin 'Uthman وهب بن بقية بن عثمان; Yonus bin 'Ubaid bin Dinar يونس بن عبيد بن دينار العبدي (Sunan Abi Dawud)
A man was with the Prophet (ﷺ) and a man passed by him and said: Messenger of Allah! I love this man. The Messenger of Allah (ﷺ) then asked: Have you informed him? He replied: No. He said: Inform him. He then went to him and said: I love you for Allah’s sake. He replied: May He for Whose sake you love me love you!
Grade: Hasan

Hadith #5200 - Sunan Abi Dawud - Abdullah bin Muslima al-Qa'nabi عبد الله بن مسلمة بن قعنب القعنبي; Anas ibn Malik; Sulaiman bin al-Mughira al-Qaysy سليمان بن المغيرة القيسي مولاهم; Thabit bin Aslam Albanani ثابت بن أسلم البناني (Sunan Abi Dawud)
When one of you meets his brother, he should salute him, then if he meets him again after a tree, wall or stone has come between them, he should also salute him. Mu’awiyah said: ‘Abd al-Wahhab b. Bakht transmitted a similar tradition to me from Abu al-Zinad, from al-A’raj, from Abu Hurairah, from the Messenger of Allah (ﷺ).
Grade: Sahih

Hadith #5226 - Sunan Abi Dawud - Abdullah bin Rbah عبد الله بن رباح الأنصاري أبو خالد; Abu Qatada ibn Rab'i; Hammad bin Zayd حماد بن زيد بن درهم الأزدي الأزرق; Musa bin Isma'il al-Munqari al-Tabudhaki موسى بن إسماعيل المنقري - لتبوذكي; Thabit bin Aslam Albanani ثابت بن أسلم البناني (Sunan Abi Dawud)
The Prophet (ﷺ) addressed me, saying: O AbuDharr! I replied: At thy service and at thy pleasure, Messenger of Allah! may I be ransom for thee.
Grade: Hasan Sahih

Hadith #5258 - Sunan Abi Dawud - Abdur Rahman bin Abi Layla عبد الرحمن بن أبي ليلى; Abu Layla; Ali bin Hashim bin al-Burayd علي بن هاشم بن البريد; Muhammad bin 'Abdur Rahman bin Abi Layla محمد بن عبد الرحمن بن أبي ليلى; Sa'id bin Sulaiman al-Dabi سعيد بن سليمان - سعدويه الضبي; Thabit bin Aslam Albanani ثابت بن أسلم البناني (Sunan Abi Dawud)
He should give it a warning three times. If it appears to him after that, he should kill it, for it is a devil.
Grade: Sahih